1978
DOI: 10.1007/bf00378889
|View full text |Cite
|
Sign up to set email alerts
|

Tierexperimentelle untersuchungen zur pathogenese intraoperativer Kreislauf- und atmungsreaktionen bei der implantation sogenannter knochenzemente in die markhöhle eines röhrenknochens

Abstract: This paper shows the effects of the increase in pressure in the medullary cavity in the blood circulation and the respiration observed during implantation of bone cement with animal experiments. The pathomechanism is also examined. The reactions of the respiration and the circulation, when observed, resulted in the intramedullary increase in pressure. These are nerval reflexes caused by the innervation in the medullary cavity and are not reactions of the monomer, which may come into the circulation during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
1
2
0
1
Order By: Relevance
“…Nervous regulation of the circulation is rapid, and hypotension may even be accompanied by bradycardia due to vagal stimulation. This assumption is also in agreement with experimental evidence that intramedullary manipulation may induce neurogenic hypotension (28).…”
Section: Cardiac Output ( I*min-1)supporting
confidence: 90%
“…Nervous regulation of the circulation is rapid, and hypotension may even be accompanied by bradycardia due to vagal stimulation. This assumption is also in agreement with experimental evidence that intramedullary manipulation may induce neurogenic hypotension (28).…”
Section: Cardiac Output ( I*min-1)supporting
confidence: 90%
“…(15,32). Klinisch manifestiert sich das Geschehen durch akute Belastungen des kleinen Kreislaufs (Anstieg des Pulmonalarteriendruckes), Abfall des arteriellen Systemdrukkes, Abfall des arteriellen 02-Partialdruckes (intrapulmonaler Shunt, vermehrte periphere Sauerstoffausschöpfung) und Anstieg des arteriellen COz-Partialdruckes, wie intraoperative hämodynamische Studien insbesondere nach Einzementierung der Femurschaftprothese zeigen konnten (1,23,24,30,31,(35)(36)(37)43). Kardiale Arrhythmien wurden ebenfalls in diesem Zusammenhang beschrieben (5,37).…”
Section: Introductionunclassified
“…65,70,71 Early during surgery, preparation and mechanical manipulation of the femoral shaft both trigger moderate autonomic reflexes while embolized cell clusters from the surgical site mediate vasoactive substances, the consequences of which contribute to pulmonary hypertension. 57,58,72,73 Bone Cement Released Methyl Methacrylate Monomer and Impact on the Coagulation System Almost 70 years have passed since monomeric methyl methacrylate (MMA) was found to cause fatal reactions during hip replacement. In the early era of bone cement implantation, studies investigating MMA found that respiratory arrest was the primary cause of death rather than cardiac arrest.…”
Section: Autopsy Findingsmentioning
confidence: 99%
“…Early during surgery, preparation and mechanical manipulation of the femoral shaft both trigger moderate autonomic reflexes while embolized cell clusters from the surgical site mediate vasoactive substances, the consequences of which contribute to pulmonary hypertension. 57 , 58 , 72 , 73 …”
Section: Bone Traumatization Venous Microembolization Thrombin and Co...mentioning
confidence: 99%